Cancer Survivors, Oncology, and Primary Care Perspectives on Survivorship Care: An Integrative Review. (June 2022) - Love, Madeleine; Debay, Marc; Hudley, Anne Charity; Sorsby, Todd; Lucero, Linda; Miller, Stuart; Sampath, Sagus; Amini, Arya; Raz, Dan; Kim, Jae; Pathak, Ranjan; Chen, Yi-Jen; et al.
Purpose: Evidence-based models of cancer survivorship care are lacking. Such models should take into account the perspectives of all stakeholders. The purpose of this integrative review is to examine the current state of the literature on cancer survivorship care from the cancer survivor, the oncology care team, and the primary care team perspectives. Methods: Using defined inclusion and exclusion criteria, we conducted a literature search of PubMed, PsycINFO, CINAHL, and Scopus databases to identify relevant articles on the stakeholders' perspectives on cancer survivorship care published between 2010 and 2021. We reviewed and abstracted eligible articles to synthesize findings. Results: A total of 21 studies were included in the review. Barriers to the receipt and provision of cancer survivorship care quality included challenges with communication, cancer care delivery, and knowledge. Conclusion: Persistent stakeholder-identified barriers continue to hinder the provision of quality cancer survivorship care. Improved communication, delivery of care, knowledge/information, and resources are needed to improve the quality of survivorship care. Novel models of cancer survivorship care that address the needs of survivors, oncology teams, and PCPs are needed.